Oxidative Weathering and Microbial Diversity of an Inactive Seafloor Hydrothermal Sulfide Chimney - Li, Jiangtao; Cui, Jiamei; Yang, Qunhui; Cui, Guojie; Wei, Bingbing; Wu, Zijun; Wang, Yong; Zhou, Huaiyang (Frontiers in Microbiology, 2017)
When its hydrothermal supply ceases, hydrothermal sulfide chimneys become inactive and commonly experience oxidative weathering on the seafloor. However, little is known about the oxidative weathering of inactive sulfide chimneys, nor about associated microbial community structures and their succession during this weathering process. In this work, an inactive sulfide chimney and an immature chimney in the early sulfate stage of formation were collected from the Main Endeavour Field of the Juan de Fuca Ridge. To assess oxidative weathering, the ultrastructures of secondary alteration products accumulating on the chimney surface were examined and the presence of possible Fe-oxidizing bacteria (FeOB) was investigated. The results of ultrastructure observation revealed that FeOB-associated ultrastructures with indicative morphologies were abundantly present. Iron oxidizers primarily consisted of members closely related to Gallionella spp. and Mariprofundus spp., indicating Fe-oxidizing species likely promote the oxidative weathering of inactive sulfide chimneys. Abiotic accumulation of Fe-rich substances further indicates that oxidative weathering is a complex, dynamic process, alternately controlled by Fe-oxidizing bacteria and by abiotic oxidization. Although hydrothermal fluid flow had ceased, inactive chimneys still accommodate an abundant and diverse microbiome whose microbial composition and metabolic potential dramatically differ from their counterparts at active vents. Bacterial lineages within current inactive chimney are dominated by members of α-, δ- and γ-Proteobacteria and they are deduced to be closely involved in a diverse set of geochemical processes including iron oxidation, nitrogen fixation, ammonia oxidation and denitrification. At last, by examining microbial communities within hydrothermal chimneys at different formation stages, a general microbial community succession can be deduced from early formation stages of a sulfate chimney to actively mature sulfide structures, and then to the final inactive altered sulfide chimney. Our findings provide valuable insights into the microbe-involved oxidative weathering process and into microbial succession occurring at inactive hydrothermal sulfide chimney after high-temperature hydrothermal fluids have ceased venting.